Oneness: East Asian conceptions of virtue, happiness, and how we are all connected - Ivanhoe, Philip J. (Oxford University Press, 2017)
Oneness with the world -- Conceptions of the self -- Selfishness and self-centeredness -- Virtues, inclinations, and oneness -- Oneness and spontaneity -- Oneness and happiness